Design, Synthesis and biochemical evaluation of novel anthracenes, ethanoanthracenes and related compounds to target Burkitt's Lymphoma - Byrne, Andrew J. (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2015)
Burkitt's lymphoma is an aggressive non-Hodgkin lymphoma occurring with high incidence in developing areas such as equatorial Africa and Papua New Guinea. Within these tropical regions of high incidence (40-50 per 10 6), Burkitt's lymphoma accounts for approximately 50% of childhood cancers and up to 90% of childhood lymphomas diagnosed. The treatment of Burkitt's lymphoma in these regions is insufficient and the development of new, safe and cost effective therapeutics are of current interest. Previous work within the Meegan and Williams groups in Trinity College Dublin identified a potent apoptotic effect induced by the (E)-1,3-bis(aryl)-2-nitro-1-propenes and the tetracyclic antidepressant maprotiline in Burkitt's lymphoma cell lines (MUTU-I and DG-75).
Keywords: Pharmacy and Pharmaceutical Sciences, Ph.D.; Ph.D. Trinity College Dublin.